THE ROLE OF COMMUNITY COUNSELORS AS CASE MANAGERS IN EMPOWERING CORRECTIONAL CLIENTS AT THE CORRECTIONAL CENTER CLASS I SURAKARTA - Chomah, Isti; Muhammad, Ali (Universitas Nusa Cendana, 2025)
This research aims to analyze the role of community counselor as case manager in empowering correctional clients at the Surakarta Class I Correctional Center. The background of this research focuses on the importance of social reintegration for post-conviction clients to restore their social identity and prevent repeat offenses. This research uses qualitative methods with data collection techniques through observation, in-depth interviews, FGDs, and literature studies and is based on Bronfenbrenner's Ecological Theory. The results showed that community counselors play an important role as mediators, facilitators, and advocates in the client reintegration process. Community support and appropriate government policies also play a crucial role in reducing social stigma and accelerating the reintegration process. However, limited resources and community stigma are the main obstacles that hinder client empowerment. A comprehensive coaching program is considered essential to increase clients' independence and reintegrate them into the community. Keywords: Empowerment ;Social Reintegration; Community Counselor